Sustainable Planet - Mission Preserve: A Serious Game for Solid Waste Management Awareness - Bezerra, Laura Ferreira [UNESP]; Pereira, Leonardo Tórtoro [UNESP]; Oliveira, Wilk; Hamari, Juho; Ranieri, Caetano Mazzoni [UNESP] (Association for Computing Machinery (ACM), 2025)
Recycling has gained global attention in recent decades. In emerging countries, recycling rates remain low despite public policy efforts. We present the prototype and initial case studies of a serious game designed to promote environmental awareness in Brazil. A quasi-experimental study (N = 32) was conducted using pre- and post-interaction questionnaires. Participants showed significant improvement in understanding sustainable practices, but no significant change in perceived knowledge or self-assessment.